The Authority of the Regional Office of the Ministry of Human Rights After Institutional Restructuring: A Fiqh al-Siyāsah Perspective - Oni Lizapahlania; Nurul Hak; Ismail Jalili (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2026)
Institutional restructuring under Presidential Regulation No. 156 of 2024 separated the Ministry of Human Rights from the Ministry of Law and Human Rights, followed by the establishment of a new organizational framework through Minister of Human Rights Regulation No. 2 of 2025. This reform redefined the authority of Regional Offices of the Ministry of Human Rights, particularly in handling alleged human rights violations at the regional level. This study examines the post-restructuring authority of Regional Offices and evaluates its implementation from the perspective of Fiqh al-Siyāsah. Using a normative-empirical legal approach based on legislation, conceptual analysis, case studies, document review, and interviews, the findings reveal that Regional Offices remain limited to administrative, coordinative, facilitative, and advisory functions without executive authority to resolve human rights violations. Consequently, effective human rights protection depends largely on inter-agency coordination. From the perspective of Fiqh al-Siyāsah, these functions reflect the principles of justice (al-'adl), public welfare (maṣlaḥah), and the protection of human dignity (karāmah al-insān). The study recommends strengthening the authority of Regional Offices through regulatory reform, institutional enhancement, and improved inter-agency coordination.